2017
DOI: 10.24200/sci.2017.4431
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Circular Dichroism Study of Gold Nanorod-Quadruplex Nanobioconjugates

Abstract: Abstract:Circular dichroism spectroscopy is a simple way to study G-quadruplex structure and is very useful for monitoring the conformational changes in G-quadruplex structure induced by modifications of the environment. Plasmonic nanoparticles with localized surface plasmon resonance (LSPR) can create strong electromagnetic fields at the surface of plasmonic metals, which remarkably influence the optical properties of molecules. Plasmonic CD is a new CD signal which originates from the dipole-dipole interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Diversity of nanostructures or material hybridized with DNA have been characterized with an increase of CD signal in the visible region. For example, AuNR with folded G-quadruplex, ssDNAs attached on the surface of Au/Ag nanocubes, cyanine dyes positioned on NP surface through DNA-templated molecular self-assembly [ 174 , 175 , 176 ]. Additionally, the fabrication of a light-driven plasmonic nanosystem, able to translate the molecular motion into reversible chiroptical was fabricated by combining azobenzene with DNA molecules [ 17 ].…”
Section: Dna/rna Based Metamaterialsmentioning
confidence: 99%
“…Diversity of nanostructures or material hybridized with DNA have been characterized with an increase of CD signal in the visible region. For example, AuNR with folded G-quadruplex, ssDNAs attached on the surface of Au/Ag nanocubes, cyanine dyes positioned on NP surface through DNA-templated molecular self-assembly [ 174 , 175 , 176 ]. Additionally, the fabrication of a light-driven plasmonic nanosystem, able to translate the molecular motion into reversible chiroptical was fabricated by combining azobenzene with DNA molecules [ 17 ].…”
Section: Dna/rna Based Metamaterialsmentioning
confidence: 99%
“…Bagheri et al 99 investigated the conjugates of AuNR with folded G-quadruplex and found the intensity increase of CD signal in the visible region. Lu et al 100 obtained a hybrid dandelion-like structure in which ssDNAs were attached on the surface of Au@Ag core/shell nanocubes and radially arranged owing to the electrostatic repulsions (Fig.…”
Section: Chiral Hybrids Of Nanoparticle and Moleculesmentioning
confidence: 99%
“…It is an innovative field at the intersection of engineering, physics, biochemistry, nanotechnology, and biotechnology, with practical applications in the design of low volume systems of fluid. Microfluidics is used in the development of inkjet printers, DNA chips, micro-propulsion, and micro-thermal technologies [24][25][26][27][28][29][30][31].…”
Section: Dielectrophoresismentioning
confidence: 99%